Comparative prospective study of the performance of chest pain scores and clinical assessment in an emergency department cohort in Singapore - Mingwei Ng; Hong Jie Gabriel Tan; Fei Gao; Jack Wei Chieh Tan; Swee Han Lim; Marcus Eng Hock Ong; R Ponampalam (Journal of the American College of Emergency Physicians Open)
Abstract Objective Chest pain scores allow emergency department (ED) physicians to identify low‐risk patients for whom discharge can be safely expedited. Although these have been extensively validated in Western cohorts, data in patients of Asian heritage are lacking. This study aimed to determine the accuracy of HEART, ED Assessment of Chest Pain Score (EDACS), and Global Registry of Acute Coronary Events (GRACE) in risk‐stratifying which chest pain patients are at risk of major adverse cardiovascular events within 30 days (composite of all‐cause mortality, acute myocardial infarction and coronary revascularization). Methods This single‐center prospective cohort‐study that enrolled 1200 patients was conducted by a large urban tertiary center in Singapore. Chest pain scores were reported before disposition by research assistants blinded to the physician's clinical assessment. Outcomes were assessed independently by a blinded cardiologist and emergency physician, while another cardiologist adjudicated in the case of discrepancies. Results Of the 1195 patients analyzed, 135 (11.3%) suffered major adverse cardiovascular events within 30 days. HEART, which ruled out major adverse cardiovascular events in 52.8% of patients with 88.1% sensitivity, and EDACS, which ruled out major adverse cardiovascular events in 57.5% of patients with 83.7% sensitivity, proved comparable to clinical judgment that ruled out major adverse cardiovascular events in 73.0% of patients with 85.5% sensitivity. GRACE was weaker—ruling out major adverse cardiovascular events in 79.2% of patients with a dismal sensitivity of 45.0%. The correlation‐statistic for HEART (79.4%) was superior to EDACS (69.9%) and GRACE (69.2%). Conclusions HEART more accurately identified low‐risk chest pain patients in an Asian ED, demonstrating comparable performance characteristics to clinical judgment. This has major implications on the use of chest pain scores to safely expedite disposition decisions for low‐risk chest pain patients.